Efektivas Penggunaan Model Pembelajaran Project Based Learning (PjBl) dengan Problem Based Learning (PBL) pada Materi Interpretasi Citra - Irnawati, Isnaini Rahmatia; Sanjoto, Tjaturahono Budi; Sriyono, Sriyono (Edu Geography, 2019)
Geography in Senior High School 1 Temanggung using lecture learning models affect to not optimal student learning outcomes esspecially to the applied matter like images interpretation. This research aims to (1) Determine the implementation of Project Based Learning and Problem Based Learning on the images interpretation matter, (2) Determine the difference efectivity of Project Based Learning and Problem Based Learning, (3) Determine classical completeness of student learning outcomes. This research used Purposive Sampling techique then determine of 64 student of X social class 2 and X social class 3 Temanggung Senior High School 1 to be sample. This research used descriptive percentage and independent sample t-test method. This research shows (1) Both of learning models implementation are suitable to the learning plan that made before, (2) Project Based Learning is more effective than Problem Based Learning according to effectiveness learning indicator , (3) Classical completeness only can reached by class that using Project Based Learning (84%), and can’t reached by class that using Problem Based Learning (78%). Pembelajaran geografi di SMA Negeri 1 Temanggung menggunakan model pembelajaran ceramah sehingga berpengaruh pada hasil belajar peserta didik yang kurang optimal terutama pada materi yang bersifat terapan seperti materi interpretasi citra. Tujuan penelitian (1) Mengetahui implementasi model pembelajaran Project Based Learning dan Problem Based Learning pada materi interpretasi citra (2) Mengetahui perbedaan efektivitas model pembelajaran Project Based Learning dan Problem Based Learning (3) Mengetahui ketuntasan klasikal hasil belajar peserta didik. Teknik sampling menggunakan teknik purposive sampling sehingga ditentukan sampel sejumlah 64 siswa kelas X IPS 2 dan X IPS 3 SMA N 1 Temanggung. Metode penelitian menggunakan deskriptif persentase dan analisis independent sample t-test. Hasil penelitian menunjukan (1) Implementasi model pembelajaran sesuai dengan RPP yang telah dibuat sebelumnya, (2) Model Project Based Learning lebih efektif dibandingkan dengan Problem Based Learning berdasarkan indikator efektivitas pembelajaran, (3) Ketuntasan Klasikal dapat dicapai oleh kelas dengan model Project Based Learning (84%), namun tidak dapat dicapai oleh kelas yang menggunakan model Problem Based Learning (78%).